Battery

By incorporating specific ratios and compositions of solid electrolyte materials in the electrolyte layers, the battery design addresses crack issues, enhancing cycle characteristics and discharge capacity while maintaining thermal stability.

JP7624631B2Active Publication Date: 2025-01-31PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021552274
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-17
Filing Date
2020-09-15
Publication Date
2025-01-31
Estimated Expiration
2040-09-15

AI Technical Summary

Technical Problem

Conventional batteries experience cracks during production, leading to decreased cycle characteristics due to the composition of their electrolytic layers, which affects their charging and discharging efficiency.

Method used

The battery design incorporates a first electrolyte layer containing a first solid electrolyte material with a mass ratio of a second solid electrolyte material between 0.05 and 1, and a second electrolyte layer with a different composition, using materials like Li, M, O, and X, and Li, M', and X', to enhance stability and conductivity.

Benefits of technology

This configuration suppresses cracks, improves cycle characteristics, and enhances discharge capacity and thermal stability, resulting in high maintenance rates of charging and discharging capacity even after multiple cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624631000002
    Figure 0007624631000002
  • Figure 0007624631000001
    Figure 0007624631000001
Patent Text Reader

Abstract

A battery 1000 according to the present disclosure comprises a positive electrode 101, a first electrolyte layer 102, a second electrolyte layer 103, and a negative electrode 104 in this order. The first electrolyte layer 102 contains a first solid electrolyte material and a second solid electrolyte material. In the first electrolyte layer 102, the mass ratio of the second solid electrolyte material to the first solid electrolyte material is greater than 0.05 and less than 1. The second electrolyte layer 103 contains the second solid electrolyte material. The first solid electrolyte material comprises Li, M, O, and X. In the first solid electrolyte material, M is at least one element selected from the group consisting of metal elements other than Li and metalloid elements, and X is at least one element selected from the group consisting of Cl, Br, and I. The second solid electrolyte material has a composition different from that of the first solid electrolyte material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to batteries. [Background technology]

[0002] Patent Document 1 discloses a battery including, in this order, a positive electrode, a first electrolyte layer containing a first solid electrolyte material, a second electrolyte layer containing a second solid electrolyte material, and a negative electrode, where the reduction potential of the second solid electrolyte material is lower than the reduction potential of the first solid electrolyte material. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2019 / 146294 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a battery having high cycle characteristics. [Means for solving the problem]

[0005] The battery according to the present disclosure comprises: a positive electrode, a first electrolyte layer, a second electrolyte layer, and a negative electrode, in that order; Where: the first electrolyte layer contains a first solid electrolyte material and a second solid electrolyte material; In the first electrolyte layer, a mass ratio of the second solid electrolyte material to the first solid electrolyte material is greater than 0.05 and less than 1; the second electrolyte layer contains the second solid electrolyte material, the first solid electrolyte material is composed of Li, M, O, and X; In the first solid electrolyte material, M is at least one element selected from the group consisting of metal elements and metalloid elements other than Li, and X is at least one element selected from the group consisting of Cl, Br, and I, and The second solid electrolyte material has a different composition than the first solid electrolyte material. Effect of the Invention

[0006] The present disclosure provides a battery with high cycle characteristics. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 shows a cross-sectional view of a battery 1000 according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0009] FIG. 1 shows a cross-sectional view of a battery 1000 according to an embodiment.

[0010] As shown in FIG. 1, a battery 1000 according to the embodiment includes a positive electrode 101, a first electrolyte layer 102, a second electrolyte layer 103, and a negative electrode 104, in this order.

[0011] The first electrolyte layer 102 contains a first solid electrolyte material and a second solid electrolyte material. In the first electrolyte layer 102, the mass ratio of the second solid electrolyte material to the first solid electrolyte material is greater than 0.05 and less than 1.

[0012] The second electrolyte layer 103 contains a second solid electrolyte material.

[0013] The second solid electrolyte material has a different composition than the first solid electrolyte material.

[0014] The first solid electrolyte material is composed of Li, M, O, and X. Here, M is at least one element selected from the group consisting of metal elements and semimetal elements other than Li. X is at least one element selected from the group consisting of Cl, Br, and I.

[0015] The battery 1000 according to the embodiment has high cycle characteristics.

[0016] A battery having high cycle characteristics is a battery that maintains a high rate of charge / discharge capacity even after multiple charge / discharge cycles.

[0017] In this disclosure, "metalloid elements" means B, Si, Ge, As, Sb, and Te.

[0018] In the present disclosure, a "metal element" is (i) All elements in groups 1 to 12 of the periodic table (except hydrogen), and (ii) All elements in groups 13 to 16 (except B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se) means...

[0019] Here, the present inventors have studied a conventional battery as disclosed in Patent Document 1, that is, a battery having a positive electrode, an electrolyte layer made of a first solid electrolyte material, an electrolyte layer made of a second solid electrolyte material, and a negative electrode in this order. The present inventors have found that in a conventional battery as disclosed in Patent Document 1, for example, cracks may occur in the electrolyte layer. These cracks occur, for example, during the manufacture of the battery. Due to the occurrence of these cracks, the cycle characteristics of the conventional battery are reduced. On the other hand, in the battery 1000 according to the embodiment, as described above, the first electrolyte layer 102 further contains not only the first solid electrolyte material but also the second solid electrolyte material contained in the second electrolyte layer 103. That is, the first electrolyte layer 102 and the second electrolyte layer 103 contain the second solid electrolyte material, which is a common material. Furthermore, in the first electrolyte layer 102, the mass ratio of the second solid electrolyte material to the first solid electrolyte material is greater than 0.05 and less than 1. Since the first electrolyte layer 102 and the second electrolyte layer have such a configuration, the battery 1000 according to the embodiment suppresses the occurrence of cracks.

[0020] In the first electrolyte layer 102, when the mass ratio of the second solid electrolyte material to the first solid electrolyte material exceeds 0.05, the occurrence of cracks can be suppressed. This improves the cycle characteristics of the battery 1000. When the mass ratio is less than 1, the internal resistance of the battery 1000 decreases. This improves the discharge capacity of the battery 1000.

[0021] The first solid electrolyte material has high ionic conductivity. Therefore, the first solid electrolyte material can be used to obtain a battery with high power output characteristics. The first solid electrolyte material also has excellent thermal stability.

[0022] The first solid electrolyte material is an example of an oxyhalide solid electrolyte. Other examples of oxyhalide solid electrolytes include a material consisting of Li, O, and X (X is at least one element selected from the group consisting of Cl, Br, and I). The first solid electrolyte material is a material containing M in addition to Li, O, and X. The first solid electrolyte material further containing M has a higher ionic conductivity than a material consisting of Li, O, and X. Therefore, the use of the first solid electrolyte material can improve the discharge capacity of the battery.

[0023] To further improve the cycle characteristics of the battery 1000, the mass ratio of the second solid electrolyte material to the first solid electrolyte material in the first electrolyte layer 102 may be greater than 0.05 and less than or equal to 0.50. To further improve the cycle characteristics of the battery 1000, the mass ratio may be greater than or equal to 0.10 and less than or equal to 0.50.

[0024] In order to increase the ionic conductivity of the first solid electrolyte material, M may contain at least one element selected from the group consisting of Nb and Ta. The molar ratio of Li to M may be 0.60 or more and 2.4 or less, and the molar ratio of O to X may be 0.16 or more and 0.35 or less. Such a first solid electrolyte material has high ionic conductivity.

[0025] The first solid electrolyte material may be a material represented by the following chemical formula (1). Li α MO β X γ (1) Here, in the chemical formula (1), the following formula 1.0≦α≦1.2, 1.0≦β≦1.3, and 3.6≦γ≦4.0, The solid electrolyte material represented by chemical formula (1) has high ionic conductivity.

[0026] In the chemical formula (1), M may be at least one element selected from the group consisting of Nb and Ta. In this case, the formula: γ=5+α-2β is satisfied in the chemical formula (1). Such a first solid electrolyte material has a higher ionic conductivity.

[0027] The first solid electrolyte material may be a material represented by the following chemical formula (3). Li x MO y X (5+x-2y) (3) Here, in chemical formula (3), the following formula 0.1 <x<7.0、および、 0.4 <y<1.9、 The solid electrolyte material represented by chemical formula (3) has high ionic conductivity.

[0028] As described above, the second solid electrolyte material has a different composition from the first solid electrolyte material. The second solid electrolyte material may have a reduction potential lower than that of the first solid electrolyte material. The second solid electrolyte material has a reduction potential lower than that of the first solid electrolyte material, thereby suppressing the reduction of the first solid electrolyte material. As described above, the first solid electrolyte material has high ionic conductivity. The suppression of the reduction of the first solid electrolyte material improves the charge / discharge efficiency of the battery 1000.

[0029] It is desirable that the first electrolyte layer 102 does not come into contact with the negative electrode 104. The electrochemically stable second electrolyte layer 103 prevents contact between the first electrolyte layer 102 and the negative electrode 104, thereby suppressing reduction of the first solid electrolyte material contained in the first electrolyte layer 102. As a result, the battery 1000 has high charge / discharge efficiency.

[0030] The voltage at which reductive decomposition of the solid electrolyte occurs (i.e., reduction potential) can be measured by the cyclic voltammetry method described in the non-patent document "Adv. EnergyMater. 2016, 20, 1501590-1501599."

[0031] The second solid electrolyte material may be a halide solid electrolyte (excluding oxyhalide solid electrolytes).

[0032] The halide solid electrolyte has high ionic conductivity and excellent thermal stability, similar to the first solid electrolyte material, and therefore the battery 1000 containing the first solid electrolyte material and the second solid electrolyte material has high output characteristics and thermal stability.

[0033] The second solid electrolyte material may be composed of Li, M', and X', where M' is at least one element selected from the group consisting of metal elements and semimetal elements other than Li, and X' is at least one element selected from the group consisting of Cl, Br, and I. Such a second solid electrolyte material has high ionic conductivity.

[0034] In order to increase the ionic conductivity of the second solid electrolyte material, M' may include Y (ie, yttrium), and the increased ionic conductivity provides the battery 1000 with a high discharge capacity.

[0035] The second solid electrolyte material containing Y is, for example, Li a Me b Y c X'6, where the formula: a+mb+3c=6 and c>0 are satisfied. Me is at least one element selected from the group consisting of metal elements and semimetal elements other than Li and Y. m represents the valence of Me.

[0036] To further increase the ionic conductivity of the second solid electrolyte material, Me may be at least one element selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, and Nb.

[0037] The second solid electrolyte material may be a material represented by the following chemical formula (2). Li 6-3z Yz X’6···(2) Here, in Chemical Formula (2), the mathematical formula: 0 < z < 2 is satisfied. The solid electrolyte material represented by Chemical Formula (2) has high ionic conductivity. The second solid electrolyte material may be Li3YCl6.

[0038] Other examples of the halide solid electrolyte are Li2MgX’4, Li2FeX’4, Li(Al, Ga, In)X’4, or Li3(Al, Ga, In)X’6. “(Al, Ga, In)” means “at least one element selected from the group consisting of Al, Ga, and In”.

[0039] To increase the discharge capacity of the battery 1000, the second solid electrolyte material may be a sulfide solid electrolyte.

[0040] Examples of the sulfide solid electrolyte used as the second solid electrolyte material are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 is. Further, LiX”, Li2O, M”O, or Li p M”O q may be added. Here, M” is at least one element selected from the group consisting of P, Si, Ge, B, Al, Ga, In, Fe, and Zn. Both p and q are natural numbers. X” is at least one element selected from the group consisting of F, Cl, Br, and I.

[0041] To increase the discharge capacity of the battery 1000, the second solid electrolyte material may contain lithium sulfide and phosphorus sulfide. The second solid electrolyte material may be Li2S-P2S5.

[0042] In order to increase the output of the battery 1000 while suppressing short-circuiting between the positive electrode 101 and the negative electrode 104, the total thickness of the first electrolyte layer 102 and the second electrolyte layer 103 may be 1 μm or more and 300 μm or less.

[0043] The first electrolyte layer 102 may have the same thickness as the second electrolyte layer 103 .

[0044] In order to increase the discharge capacity of the battery 1000, the total mass ratio of the first solid electrolyte material and the second solid electrolyte material to the entire first electrolyte layer 102 may be 70% or more, or 90% or more, in the first electrolyte layer 102. In order to increase the discharge capacity of the battery 1000, the first electrolyte layer 102 may be composed of only the first solid electrolyte material and the second solid electrolyte material.

[0045] In order to increase the discharge capacity of the battery 1000, the mass ratio of the second solid electrolyte material to the entire second electrolyte layer 103 may be 70% or more, or 90% or more, in the second electrolyte layer 103. In order to increase the discharge capacity of the battery 1000, the second electrolyte layer 103 may be made of only the second solid electrolyte material.

[0046] The positive electrode 101 contains a positive electrode active material and an electrolyte material.

[0047] The positive electrode active material is a material capable of absorbing and releasing metal ions such as lithium ions.

[0048] Examples of the positive electrode active material include lithium-containing transition metal oxides, transition metal fluorides, polyanions, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfides, or transition metal oxynitrides. Examples of the lithium-containing transition metal oxides include Li(NiCoAl)O2, Li(NiCoMn)O2, or LiCoO2. By using the lithium-containing transition metal oxides as the positive electrode active material, the manufacturing cost can be reduced and the average discharge voltage of the battery 1000 can be increased.

[0049] To achieve higher discharge capacity and energy density of the battery, the positive electrode active material may be lithium nickel-cobalt-manganese oxide.

[0050] The positive electrode 101 may contain positive electrode active material particles as the positive electrode active material. In this case, the positive electrode active material may have a median diameter of 0.1 μm or more and 100 μm or less. When the positive electrode active material has a median diameter of 0.1 μm or more, the positive electrode active material and the electrolyte material can be well dispersed in the positive electrode 101. This improves the charge / discharge characteristics of the battery 1000. When the positive electrode active material has a median diameter of 100 μm or less, the lithium diffusion rate in the positive electrode active material improves. This allows the battery to operate at a high output.

[0051] The electrolyte material contained in the positive electrode 101 is, for example, a solid electrolyte.

[0052] The electrolyte material contained in the positive electrode 101 may be a first solid electrolyte material. That is, the positive electrode 101 may contain the first solid electrolyte material. When the positive electrode 101 contains the same material as the first electrolyte layer 102, the charge / discharge capacity and output characteristics of the battery are improved.

[0053] Hereinafter, a material different from the first solid electrolyte material and the second solid electrolyte material will be referred to as a third solid electrolyte material.

[0054] The positive electrode 101 may contain a second solid electrolyte material or a third solid electrolyte material.

[0055] The third solid electrolyte material may be a sulfide solid electrolyte.

[0056] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 These include LiX”, Li2O, and M”O. q , or Lip M”O q may be added. Here, X″ is at least one element selected from the group consisting of F, Cl, Br, and I. M″ is at least one element selected from the group consisting of P, Si, Ge, B, Al, Ga, In, Fe, and Zn. p and q are both natural numbers.

[0057] The third solid electrolyte material may be an oxide solid electrolyte.

[0058] Examples of oxide solid electrolytes include: (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or elemental substitutions thereof; (ii) (LaLi)TiO3-based perovskite-type solid electrolytes, (iii) Li 14 ZnGeO 16 LISICON-type solid electrolytes such as Li4SiO4, LiGeO4 and their elemental substitutions; (iv) Li7La3Zr2O 12 or an element-substituted garnet-type solid electrolyte; (v) Li3PO4 or its N-substituted derivatives, or (vi) Glasses or glass ceramics containing Li-BO compounds such as LiBO2 or Li3BO3 with the addition of Li2SO4 or Li2CO3 It is.

[0059] The third solid electrolyte material may be a polymer solid electrolyte.

[0060] Examples of the polymer solid electrolyte include a polymer compound and a lithium salt compound. The polymer compound may have an ethylene oxide structure. The polymer compound having an ethylene oxide structure can contain a large amount of lithium salt, and therefore can further increase the ionic conductivity.

[0061] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.

[0062] The third solid electrolyte material may be a complex hydride solid electrolyte.

[0063] Examples of complex hydride solid electrolytes are LiBH4-LiI or LiBH4-P2S5.

[0064] The third solid electrolyte material may be an oxyhalide solid electrolyte different from the first solid electrolyte material. Examples of oxyhalide solid electrolytes are Li3OX″ or Li2HOX″, where X″ is at least one element selected from the group consisting of F, Cl, Br, and I.

[0065] The shape of the electrolyte material contained in the positive electrode 101 is not limited. Examples of the shape include a needle shape, a sphere shape, or an oval sphere shape. For example, the electrolyte material may be in the form of particles.

[0066] When the electrolyte material contained in the positive electrode 101 is particulate (e.g., spherical), the median diameter of the electrolyte material may be 100 μm or less, or may be 10 μm or less. This allows the positive electrode active material and the electrolyte material to be well dispersed in the positive electrode 101. Due to this good dispersion, the battery has high charge / discharge characteristics.

[0067] The electrolyte material contained in the positive electrode 101 may have a smaller median diameter than the positive electrode active material. This allows the electrolyte material and the positive electrode active material to be better dispersed in the positive electrode 101. Due to this better dispersion, the battery has high charge / discharge efficiency.

[0068] To increase the energy density and output of the battery 1000, in the positive electrode 101, the ratio of the volume of the positive electrode active material to the sum of the volume of the positive electrode active material and the volume of the electrolyte material may be 0.30 or more and 0.95 or less.

[0069] To increase the energy density and output of the battery 1000, the positive electrode 101 may have a thickness of 10 μm or more and 500 μm or less.

[0070] The negative electrode 104 contains a negative electrode active material and an electrolyte material.

[0071] The negative electrode active material is a material capable of absorbing and releasing metal ions such as lithium ions.

[0072] Examples of the negative electrode active material are metal materials, carbon materials, oxides, nitrides, tin compounds, or silicon compounds. The metal material may be a single metal or an alloy. Examples of the metal material are lithium metal or a lithium alloy. Examples of the carbon material are natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, or amorphous carbon. From the viewpoint of capacity density, suitable examples of the negative electrode active material are silicon (i.e., Si), tin (i.e., Sn), silicon compounds, or tin compounds.

[0073] The negative electrode 104 may contain negative electrode active material particles as the negative electrode active material. In this case, the negative electrode active material may have a median diameter of 0.1 μm or more and 100 μm or less. When the negative electrode active material has a median diameter of 0.1 μm or more, the negative electrode active material and the electrolyte material can be well dispersed in the negative electrode 104. This improves the charge / discharge characteristics of the battery. When the negative electrode active material has a median diameter of 100 μm or less, the lithium diffusion rate in the negative electrode active material improves. This allows the battery to operate at high output.

[0074] The electrolyte material contained in the negative electrode 104 is, for example, a solid electrolyte.

[0075] The electrolyte material contained in the negative electrode 104 may be a second solid electrolyte material. That is, the negative electrode 104 may contain the second solid electrolyte material.

[0076] The electrolyte material contained in the negative electrode 104 may be the third solid electrolyte material described above.

[0077] The shape of the electrolyte material contained in the negative electrode 104 is not limited. Examples of the shape include a needle shape, a sphere shape, or an oval sphere shape. For example, the electrolyte material may be in the form of particles.

[0078] When the electrolyte material contained in the negative electrode 104 is particulate (e.g., spherical), the median diameter of the electrolyte material may be 100 μm or less, or may be 10 μm or less. This allows the negative electrode active material and the electrolyte material to be well dispersed in the negative electrode 104. Due to this good dispersion, the battery has high charge / discharge characteristics.

[0079] The electrolyte material contained in the negative electrode 104 may have a smaller median diameter than the negative electrode active material. This allows the electrolyte material and the negative electrode active material to be well dispersed in the negative electrode 104. Due to this well dispersion, the battery has high charge / discharge efficiency.

[0080] From the viewpoint of the energy density and output of the battery, in the negative electrode 104, the ratio of the volume of the negative electrode active material to the total volume of the negative electrode active material and the electrolyte material may be 0.30 or more and 0.95 or less.

[0081] In order to increase the energy density and power output of the battery, the negative electrode 104 may have a thickness of 10 μm or more and 500 μm or less.

[0082] At least a part of the surface of the positive electrode active material or at least a part of the surface of the negative electrode active material may be covered with a covering material in order to reduce the interface resistance.

[0083] A material with low electronic conductivity may be used as the coating material. Examples of the coating material include the sulfide solid electrolyte, polymer solid electrolyte, complex hydride solid electrolyte, or halide solid electrolyte, which are exemplified as the third solid electrolyte material. From the viewpoint of potential stability, a suitable example of the coating material is an oxide solid electrolyte. By using an oxide solid electrolyte as the coating material, the battery has a higher charge / discharge efficiency.

[0084] Other examples of oxide solid electrolytes that can be used as coating materials include: (i) Li-Nb-O compounds such as LiNbO3; (ii) Li-BO compounds such as LiBO2 or Li3BO3; (iii) Li-Al-O compounds such as LiAlO2; (iv) Li-Si-O compounds such as Li4SiO4; (v) Li2SO4 or Li4Ti5O 12 Li-Ti-O compounds such as (vi) Li-Zr-O compounds such as Li2ZrO3; (vii) Li-Mo-O compounds such as Li2MoO3; (viii) Li-VO compounds such as LiV2O5, or (ix) Li-WO compounds such as Li2WO4 It is.

[0085] In order to increase the output of the battery, at least one selected from the group consisting of the first electrolyte layer 102 and the second electrolyte layer 103 may contain the third solid electrolyte material described above.

[0086] At least one selected from the group consisting of the positive electrode 101, the first electrolyte layer 102, the second electrolyte layer 103, and the negative electrode 104 may contain a nonaqueous electrolyte solution, a gel electrolyte, or an ionic liquid in order to facilitate the exchange of lithium ions and improve the output characteristics of the battery.

[0087] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.

[0088] Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, or fluorine solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate, or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane, or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorine solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, or fluorodimethylene carbonate. One type of non-aqueous solvent selected from these may be used alone, or a mixture of two or more types of non-aqueous solvents selected from these may be used.

[0089] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.

[0090] The concentration of the lithium salt is, for example, in the range of 0.5 mol / liter to 2 mol / liter.

[0091] The gel electrolyte may be a polymer material impregnated with a non-aqueous electrolyte, such as polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.

[0092] Examples of cations contained in ionic liquids are: (i) Aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium salts, (ii) aliphatic cyclic ammonium such as pyrrolidiniums, morpholiniums, imidazoliniums, tetrahydropyrimidiniums, piperaziniums, or piperidiniums, or (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridiniums or imidazoliums.

[0093] An example of an anion contained in an ionic liquid is PF6 - , BF4 - , SbF6 - , AsF6 - , SO3CF3 - , N(SO2CF3)2 - , N(SO2C2F5)2 - , N(SO2CF3)(SO2C4F9) - , or C(SO2CF3)3 - The ionic liquid may contain a lithium salt.

[0094] At least one selected from the group consisting of the positive electrode 101, the first electrolyte layer 102, the second electrolyte layer 103, and the negative electrode 104 may contain a binder to improve adhesion between particles.

[0095] Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, and carboxymethyl cellulose.

[0096] Copolymers can also be used as binders. Examples of such binders are copolymers of two or more materials selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkylvinylether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethylvinylether, acrylic acid, and hexadiene. A mixture of two or more materials selected from the above materials may also be used as binders.

[0097] At least one selected from the positive electrode 101 and the negative electrode 104 may contain a conductive assistant to enhance electronic conductivity.

[0098] Examples of the conductive additive include: (i) graphite, such as natural or synthetic graphite; (ii) carbon black, such as acetylene black or ketjen black; (iii) conductive fibers, such as carbon or metal fibers; (iv) fluorocarbons, (v) metal powders such as aluminum; (vi) conductive whiskers such as zinc oxide or potassium titanate; (vii) a conductive metal oxide, such as titanium dioxide; or (viii) Conductive polymers such as polyaniline, polypyrrole, or polythiophene In order to reduce costs, the above-mentioned conductive assistant (i) or (ii) may be used.

[0099] Examples of the shape of the battery according to the first embodiment are a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, or a laminate type.

[0100] <Method for producing the first solid electrolyte material> The first solid electrolyte material is produced, for example, by the following method.

[0101] The raw material powders are mixed to have the desired composition. Examples of raw material powders are oxides, hydroxides, halides, or oxyhalides.

[0102] As an example, when the desired composition is LiNbOCl4, the raw material powders LiCl and NbOCl3 are mixed in a molar ratio of 1:1.

[0103] The selection of the raw material powder determines the elements M and X. The molar ratio of the raw material powder and the synthesis process are adjusted to determine the molar fraction of the elements constituting the first solid electrolyte material.

[0104] The raw material powders may be mixed in a pre-adjusted molar ratio to offset compositional changes that may occur during the synthesis process.

[0105] The raw material powders are mixed to obtain a mixed powder. The mixed powders are reacted with each other mechanochemically (i.e., by a method of mechanochemical milling) in a mixing device such as a planetary ball mill to obtain a reactant. The reactant may be fired in a vacuum or in an inert gas atmosphere (e.g., an argon atmosphere or a nitrogen atmosphere). Alternatively, the mixed powder may be sintered in a vacuum or in an inert atmosphere to obtain a reactant. By these methods, a first solid electrolyte material is obtained.

[0106] The composition of the first solid electrolyte material can be determined by an analysis method such as inductively coupled plasma optical emission spectrometry (i.e., ICP optical emission spectrometry), ion chromatography, inert gas fusion-infrared absorption spectrometry, or EPMA (Electron Probe Micro Analyzer). However, the amount of oxygen may include an error of about 10% due to low measurement accuracy.

[0107] <Method for producing the second solid electrolyte material> The second solid electrolyte material is produced, for example, by the following method.

[0108] The raw material powders are mixed to have a desired composition. An example of the raw material powders is a halide.

[0109] As an example, if the desired composition is Li3YCl4, the raw material powders LiCl and YCl3 are mixed in a molar ratio of 3:1.

[0110] The elements constituting the second solid electrolyte material are determined by the selection of the raw material powders. The mole fractions of the elements constituting the second solid electrolyte material are determined by adjusting the molar ratio of the raw material powders and the synthesis process.

[0111] The raw material powders may be mixed in a pre-adjusted molar ratio to offset compositional changes that may occur during the synthesis process.

[0112] The raw material powders are mixed to obtain a mixed powder. The mixed powders are reacted with each other mechanochemically (i.e., by a method of mechanochemical milling) in a mixing device such as a planetary ball mill to obtain a reactant. The reactant may be fired in a vacuum or in an inert gas atmosphere (e.g., an argon atmosphere or a nitrogen atmosphere). Alternatively, the mixed powder may be sintered in a vacuum or in an inert atmosphere to obtain a reactant. By these methods, a second solid electrolyte material is obtained.

[0113] The composition of the second solid electrolyte material can be determined by an analytical method such as, for example, ICP emission spectroscopy, ion chromatography, inert gas fusion-infrared absorption spectroscopy, or EPMA. EXAMPLES

[0114] The present disclosure will now be described in more detail with reference to the following examples.

[0115] Example 1 [Preparation of the first solid electrolyte material] In a dry atmosphere having a dew point of -30°C or less (hereinafter referred to as "dry atmosphere"), Li2O2 and TaCl5 were prepared as raw material powders so as to have a Li2O2:TaCl5 molar ratio of 1:2. These raw material powders were pulverized in a mortar to obtain a mixed powder. The obtained mixed powder was treated to cause a mechanochemical reaction for 24 hours at 600 rpm using a planetary ball mill (Fritsch, P-7 type). The mixed powder was then fired at 200°C for 6 hours. In this manner, a powder of the first solid electrolyte material according to Example 1 was obtained. The first solid electrolyte material according to Example 1 is composed of Li 1.2 TaO 1.3 Cl 3.6 The composition was represented by the formula:

[0116] [Preparation of the second solid electrolyte material] In a dry atmosphere, LiCl and YCl3 were prepared as raw material powders so that the LiCl:YCl3 molar ratio was 3:1. Except for this, the second solid electrolyte material according to Example 1 was obtained in the same manner as the first solid electrolyte material according to Example 1. The second solid electrolyte material according to Example 1 had a composition represented by Li3YCl6.

[0117] [Measurement of reduction potential of the first solid electrolyte material and the second solid electrolyte material] The reduction potentials of the first and second solid electrolyte materials according to Example 1 were measured by cyclic voltammetry. Specifically, the reduction potentials were measured by the following method.

[0118] In an insulating cylinder having an inner diameter of 9.5 mm, SUS foil, a solid electrolyte material (100 mg), and Li foil were laminated in this order. A pressure of 360 MPa was applied to this laminate. Then, current collectors made of stainless steel were attached to the top and bottom of the laminate, and current collecting leads were attached to the current collectors. Finally, the inside of the insulating cylinder was isolated from the outside atmosphere and sealed using an insulating ferrule. In this way, a potential measurement cell was obtained.

[0119] The potential measurement cell was placed in a thermostatic bath at 25° C. The potential was scanned at a sweep rate of 5 mV / s from −0.5 V to 6 V with respect to the Li reference potential by cyclic voltammetry measurement.

[0120] As a result, the first solid electrolyte material according to Example 1 had a reduction potential of 2.3 V. The second solid electrolyte material according to Example 1 had a reduction potential of 0.3 V.

[0121] [Preparation of electrolyte mixture] The first solid electrolyte material according to Example 1 and the second solid electrolyte material according to Example 1 were prepared in a mass ratio of 10:1. These materials were mixed in an agate mortar. In this manner, the electrolyte mixture according to Example 1 was obtained.

[0122] [Preparation of positive electrode material] In a dry atmosphere, the first solid electrolyte material according to Example 1 and LiCoO2 (hereinafter referred to as "LCO") were prepared in a volume ratio of 30:70. These materials were mixed in an agate mortar. In this manner, the positive electrode material according to Example 1 was obtained.

[0123] [Battery construction] In an insulating cylinder having an inner diameter of 9.5 mm, the positive electrode material (10 mg) of Example 1, the electrolyte mixture (80 mg) of Example 1, and the second solid electrolyte material (80 mg) of Example 1 were laminated in this order to obtain a laminate. A pressure of 360 MPa was applied to this laminate to form a positive electrode, a first electrolyte layer, and a second electrolyte layer.

[0124] Next, aluminum powder (20 mg) was layered on the positive electrode, and a pressure of 360 MPa was applied to this layered body to form a positive electrode current collector.

[0125] Next, metal In foil (thickness 200 μm), metal Li foil (thickness 300 μm), and metal In foil (thickness 200 μm) were laminated on the second electrolyte layer in this order to obtain a laminate. A pressure of 80 MPa was applied to this laminate to form a negative electrode. A current collector made of stainless steel was placed on the positive electrode current collector and the negative electrode, and a current collecting lead was attached to the current collector made of stainless steel.

[0126] Finally, the inside of the insulating cylinder was isolated from the outside atmosphere by using an insulating ferrule, and the inside of the cylinder was sealed. In this manner, the battery according to Example 1 was obtained.

[0127] Example 2 [Preparation of the first solid electrolyte material] In a dry atmosphere, LiCl and NbOCl3 were prepared as raw material powders so that the molar ratio of LiCl:NbOCl3 was 1:1. These raw material powders were pulverized in a mortar to obtain a mixed powder. The obtained mixed powder was treated to mechanochemically react using a planetary ball mill at 600 rpm for 24 hours. In this manner, a powder of the first solid electrolyte material according to Example 2 was obtained. The first solid electrolyte material according to Example 2 had a composition represented by LiNbOCl4.

[0128] [Measurement of reduction potential of the first solid electrolyte material] The reduction potential of the first solid electrolyte material according to Example 2 was measured in the same manner as in Example 1. The first solid electrolyte material according to Example 2 had a reduction potential of 2.9V.

[0129] [Preparation of electrolyte mixture] The first solid electrolyte material according to Example 2 and the second solid electrolyte material according to Example 1 were prepared in a mass ratio of 10:2. These materials were mixed in an agate mortar. In this manner, the electrolyte mixture according to Example 2 was obtained.

[0130] [Preparation of positive electrode material] In a dry atmosphere, the first solid electrolyte material according to Example 2 and LCO were prepared in a mass ratio of 30:70. These materials were mixed in an agate mortar. In this manner, the positive electrode material according to Example 2 was obtained.

[0131] [Battery construction] A battery according to Example 2 was obtained in the same manner as in Example 1, except that the electrolyte mixture according to Example 2 was used instead of the electrolyte mixture according to Example 1.

[0132] Example 3 [Preparation of electrolyte mixture] The first solid electrolyte material according to Example 1 and the second solid electrolyte material according to Example 1 were prepared in a mass ratio of 10:5. These materials were mixed in an agate mortar. In this manner, the electrolyte mixture according to Example 3 was obtained.

[0133] [Battery construction] A battery according to Example 3 was obtained in the same manner as in Example 1, except that the electrolyte mixture according to Example 3 was used instead of the electrolyte mixture according to Example 1.

[0134] Example 4 [Preparation of the second solid electrolyte material] In an argon atmosphere having a dew point of -60°C or less (hereinafter referred to as "dry argon atmosphere"), Li2S and P2S5 were prepared as raw material powders so as to have a Li2S:P2S5 molar ratio of 75:25. These raw material powders were pulverized in a mortar to obtain a mixed powder. The mixed powder was then treated to react mechanochemically for 10 hours at 510 rpm using a planetary ball mill. In this way, a glassy solid electrolyte was obtained. The obtained glassy solid electrolyte was heat-treated at 270°C for 2 hours in a dry argon atmosphere. In this way, a powder of the second solid electrolyte material according to Example 4, which is a glass-ceramic solid electrolyte, was obtained. The second solid electrolyte material according to Example 4 was a glassy solid electrolyte represented by Li2S-P2S5.

[0135] [Measurement of reduction potential of second solid electrolyte material] The reduction potential of the second solid electrolyte material according to Example 4 was measured in the same manner as in Example 1. The second solid electrolyte material according to Example 4 was stable against lithium.

[0136] [Preparation of electrolyte mixture] The first solid electrolyte material according to Example 1 and the second solid electrolyte material according to Example 4 were prepared in a mass ratio of 10:5. These materials were mixed in an agate mortar. In this manner, the electrolyte mixture according to Example 4 was obtained.

[0137] [Battery construction] A battery according to Example 4 was obtained in the same manner as in Example 1, except that the electrolyte mixture according to Example 4 and the second solid electrolyte material according to Example 4 were used instead of the electrolyte mixture according to Example 1 and the second solid electrolyte material according to Example 1.

[0138] Comparative Example 1 [Preparation of electrolyte mixture] The first solid electrolyte material according to Example 1 and the second solid electrolyte material according to Example 1 were prepared in a weight ratio of 10:0.5. These materials were mixed in an agate mortar. In this manner, an electrolyte mixture according to Comparative Example 1 was obtained.

[0139] [Battery construction] A battery according to Comparative Example 1 was obtained in the same manner as in Example 1, except that the electrolyte mixture according to Comparative Example 1 was used instead of the electrolyte mixture according to Example 1.

[0140] Comparative Example 2 [Battery construction] A battery according to Comparative Example 2 was obtained in the same manner as in Example 1, except that the first solid electrolyte material according to Example 1 was used instead of the electrolyte mixture according to Example 1. That is, the first electrolyte layer according to Comparative Example 2 contained only the first solid electrolyte material of Example 1, and did not contain the second solid electrolyte material.

[0141] [Charge / discharge test] Charge and discharge tests of the batteries obtained in Examples 1 to 4, Comparative Example 1, and Comparative Example 2 were carried out under the following conditions.

[0142] The resulting battery was placed in a thermostatic chamber at 25°C.

[0143] The battery was charged at a current of 360 μA, which corresponds to a 0.3 C rate, until the voltage reached 4.2 V. The battery was then discharged at a current of 360 μA, which corresponds to a 0.3 C rate, until the voltage reached 3.1 V.

[0144] The above-mentioned charging and discharging was counted as one charge-discharge cycle, and the charge-discharge cycle was repeated 25 times.

[0145] The alloy of metallic In and metallic Li used in the negative electrode of the battery has a potential of 0.6 V vs. lithium.

[0146] From the above charge / discharge tests, the discharge capacity retention rates of the batteries according to Examples 1 to 4, Comparative Example 1, and Comparative Example 2 were calculated. The discharge capacity retention rate represents the ratio of the discharge capacity after 25 cycles to the initial discharge capacity. The values ​​of the discharge capacity retention rate are shown in Table 1. In Table 1, the mass ratio of the second solid electrolyte material to the first solid electrolyte material in the first electrolyte layer is expressed as the mass ratio of the electrolyte mixture.

[0147] [Table 1]

[0148] ≪Consideration≫ As is clear from Table 1, the batteries according to Examples 1 to 4 have a high discharge capacity retention rate, that is, the batteries according to Examples 1 to 4 have high cycle characteristics.

[0149] As is clear from a comparison of the batteries of Examples 1 and 3 with the batteries of Comparative Examples 1 and 2, the batteries in which the mass ratio of the second solid electrolyte material to the first solid electrolyte material in the first electrolyte layer is 0.05 or less have a low discharge capacity retention rate.

[0150] As is clear from a comparison between the batteries of Example 3 and Example 4, when the second solid electrolyte material is a sulfide solid electrolyte or a halide solid electrolyte, a battery having a high discharge capacity retention rate can be obtained. [Industrial Applicability]

[0151] The battery of the present disclosure can be used, for example, as an all-solid-state lithium-ion secondary battery. [Explanation of symbols]

[0152] 1000 batteries 101 Positive electrode 102 First electrolyte layer 103 Second electrolyte layer 104 Negative electrode

Claims

1. a positive electrode, a first electrolyte layer, a second electrolyte layer, and a negative electrode, in this order; Where: the first electrolyte layer contains a first solid electrolyte material and a second solid electrolyte material, and a total mass ratio of the first solid electrolyte material and the second solid electrolyte material to the entire first electrolyte layer is 70% or more; In the first electrolyte layer, a mass ratio of the second solid electrolyte material to the first solid electrolyte material is 0.10 or more and 0.50 or less; the second electrolyte layer contains the second solid electrolyte material, and a mass ratio of the second solid electrolyte material to the entire second electrolyte layer is 70% or more; the first solid electrolyte material is composed of Li, M, O, and X; In the first solid electrolyte material, M is at least one element selected from the group consisting of metal elements and metalloid elements other than Li, and X is at least one element selected from the group consisting of Cl, Br, and I, and The second solid electrolyte material has a different composition from the first solid electrolyte material. battery.

2. The reduction potential of the second solid electrolyte material is lower than the reduction potential of the first solid electrolyte material.

10. The battery of claim 1.

3. M contains at least one element selected from the group consisting of Nb and Ta; 3. The battery of claim 1 or 2.

4. The first solid electrolyte material is represented by the following chemical formula (1): Li α MO β X γ ・・・(1) Here, the following formula: 1.0≦α≦1.2, 1.0≦β≦1.3, and 3.6≦γ≦4.0, is satisfied, The battery of any one of claims 1 to 3.

5. M is at least one element selected from the group consisting of Nb and Ta; The formula: γ=5+α-2β is satisfied.

5. The battery of claim 4.

6. the second solid electrolyte material is composed of Li, M', and X'; Where: M' is at least one element selected from the group consisting of metal elements and metalloid elements other than Li, X' is at least one element selected from the group consisting of Cl, Br, and I; The battery of any one of claims 1 to 5.

7. M' comprises yttrium; 7. The battery of claim 6.

8. The second solid electrolyte material is represented by the following chemical formula (2): Li 6-3z Y z X' 6 ・・・(22) where the mathematical expression: 0<z<2 is satisfied.

8. The battery of claim 7.

9. The second solid electrolyte material is Li 3 Y.C.L. 6 That is, 9. The battery of claim 8.

10. The second solid electrolyte material is a sulfide solid electrolyte. The battery of any one of claims 1 to 5.

11. The sulfide solid electrolyte contains lithium sulfide and phosphorus sulfide. The battery of claim 10.

12. The sulfide solid electrolyte is Li 2 S-P 2 S 5 That is, 12. The battery of claim 10 or 11.

13. The positive electrode contains the first solid electrolyte material.

13. The battery of claim 1.

Citation Information

Patent Citations

  • Secondary battery and method for manufacturing secondary battery

    JP2016219291A

  • Battery, and battery manufacturing method

    JP2017199668A

  • Battery

    WO2019135323A1

  • Battery

    WO2019146217A1

  • Battery

    WO2019146294A1